The role of intermediaries in sectoral innovation system: The case of Thailand's food industry. (1st March 2014) - Chunhavuthiyanon, Manunya; Intarakumnerd, Patarapong
Unlike previous snapshot studies, this research traces 'historical learning events' to enable us to examine the evolution of roles and underpinning capabilities of intermediaries in an innovation system. By following this approach, the rationale, obstacles and lessons learned of intermediaries in performing their roles and building up required capabilities can be vividly illustrated. The National Food Institute (NFI) of Thailand was selected as the case study. As an intermediary organization, NFI has enhanced its capabilities step by step in analysing and disseminating information, training, testing policy development and consultancies through major 'learning events' that provide NFI with learning opportunities. As a result, over time it can perform its intermediary roles better by reducing 'systemic failures' in the Thai food industry's sectoral innovation system. Recently, however, due to the lack of an official mandate, continuous government budgetary support and organizational lock-in problems, NFI's role has not evolved with the changes in strategies and capability needs of Thai food exporters as these firms change from OEM to OBM manufacturers.